Effect of the Friction Coefficient on the Efficiency of Goods Handling in Warehouses - Delia Meldra; Zefri Azharman (Greeners: Journal of Green Engineering for Sustainability, 2026)
This study is motivated by the importance of efficiency in material handling within warehouse logistics systems, which is influenced by physical factors, particularly the coefficient of friction of floor surfaces. The objective of this research is to analyze the effect of the coefficient of friction on pushing force and the operational efficiency of material handling in warehouses. The method employed is a direct experimental approach by moving a 10 kg load using a trolley over a distance of 5 meters on three types of surfaces: ceramic, wood, and carpet. Each treatment was repeated 20 times. The observed variables include pushing force, travel time, work, efficiency, and coefficient of friction, which were subsequently analyzed using descriptive and inferential statistics. The results indicate that an increase in the coefficient of friction significantly increases the required pushing force and travel time, while reducing system efficiency. The ANOVA test produced a significance value of 0.000 (<0.05), indicating a significant difference among the surface types. Furthermore, Pearson correlation analysis revealed a very strong relationship between the coefficient of friction and pushing force (r = 0.990). Ceramic surfaces yielded the highest efficiency compared to wood and carpet. The study concludes that selecting floor materials with a low coefficient of friction can significantly improve the operational efficiency of material handling in warehouses, making it an important consideration in logistics system design.